Multilevel Effects of Competence, Work Motivation, Clinical Leadership, and Management Support on Human Resource Service Capability within Corporate Clinic Networks - Pritasari, Devi Desianti; Permana, Andy Hamzah (Dinasti Publisher, 2026)
The rapid growth of corporate clinic networks requires human resources (HR) to be well-prepared to deliver high-quality, professional, and patient-centered services. IHC Clinics have experienced significant increases in service volume, network expansion, and patient visits. These developments have created a need to strengthen HR service capabilities to ensure consistent service quality across all clinics. This study aims to analyze the influence of HR competency, work motivation, clinic leadership, and management support on HR service capability within the IHC clinic network. A quantitative explanatory research design was employed. Data were collected through a survey involving 293 respondents from 33 clinics. Hierarchical Linear Modeling (HLM) was used to examine the simultaneous effects of individual-level and organizational-level factors on HR service capability. The findings indicate that HR competency, work motivation, clinic leadership, and management support have significant positive effects on HR service capability. Among these variables, work motivation exerts the strongest influence. Furthermore, the results reveal that individual-level factors contribute more substantially than organizational-level factors in explaining variations in HR service capability across clinics. These findings suggest that strengthening HR service capability requires competency development, enhanced work motivation, effective clinic leadership, and strong management support.